Applications of porphyrinoids as functional materials - Lang, Heinrich, active 1985; Rüffer, Tobias, 1968- (RSC smart materials, 2021)
"Porphyrinoids are pyrrole-containing macrocycles with varied core sizes, which have found many applications beyond the original chemical and biological aspects. Porphyrin research has a long history, covering a wide variety of disciplines of natural sciences, including photosynthesis, P450-related biocatalysis, organic photovoltaic cells, photodynamic therapeutic agents, bioimaging probes, chemosensors, conductive organic materials, light-emitting materials, near-infrared dyes, nonlinear optical materials, information storage, molecular wires, and metal ligands. This book gives an overview of the applications and potential applications of porphyrins and related macrocycles as smart or functional materials. Chapters cover applications in fields such as energy storage and transfer, water purification, molecular electronics and imaging. With contributions from leading global researchers, this title will be of interest to graduate students and researchers across materials science, chemistry, physics and medicine"--Print version, page 4 of cover.